Conversion disorders - Gordon, Amy, author; Candelaria Fletcher, Harrison, advisor; Perry, Sarah, committee member; Romagni, Domenica, committee member (Colorado State University. Libraries, 2025)
Conversion Disorders is a memoir exploring the impact of a debilitating illness on the narrator's conceptions of self. The novel traces the narrator, a lawyer in the U.S. Army, from Iraq to Hawaii to New York, as she suffers from a constellation of physical and cognitive symptoms with no apparent medical cause. She spends weeks in hospitals, including a stay in an in-patient psychiatric facility, where she is scared, lonely, and grappling with questions of identity and with the uncertainty of not knowing what is wrong. Her eventual diagnosis of conversion disorder, a disorder rooted in the mind and the modern-day incarnation of hysteria, forces the narrator to reimagine her understanding of herself and the connection between her mind and body. Questioning if she is the person she thought she was, or at least the person she aspired to be, she contemplates her childhood and family, her itinerant adulthood, and the consequences of a mind that can betray a body. At its core, this is a memoir about frailty and identity, about what happens when you stop knowing yourself.